Low band gap frequencies and multiplexing properties in 1D and 2D mass spring structures. (30th September 2016) - Aly, Arafa H; Mehaney, Ahmed
Abstract: This study reports on the propagation of elastic waves in 1D and 2D mass spring structures. An analytical and computation model is presented for the 1D and 2D mass spring systems with different examples. An enhancement in the band gap values was obtained by modeling the structures to obtain low frequency band gaps at small dimensions. Additionally, the evolution of the band gap as a function of mass value is discussed. Special attention is devoted to the local resonance property in frequency ranges within the gaps in the band structure for the corresponding infinite periodic lattice in the 1D and 2D mass spring system. A linear defect formed of a row of specific masses produces an elastic waveguide that transmits at the narrow pass band frequency. The frequency of the waveguides can be selected by adjusting the mass and stiffness coefficients of the materials constituting the waveguide. Moreover, we pay more attention to analyze the wave multiplexer and DE-multiplexer in the 2D mass spring system. We show that two of these tunable waveguides with alternating materials can be employed to filter and separate specific frequencies from a broad band input signal. The presented simulation data is validated through comparison with the published research, and can be extended in the development of resonators and MEMS verification.